(untitled) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
This study examines the effectiveness of modern pedagogical technologies in enhancing student autonomy within higher education. The research focuses on the integration of digital platforms, interactive teaching methods, project-based learning, problem-based learning, and reflective practices. A mixed-method approach, including surveys, observations, and experimental comparison, was employed to evaluate their impact. The findings indicate that the systematic implementation of innovative teaching technologies significantly improves students’ motivation, independent learning skills, critical thinking, and self-assessment abilities. The experimental results demonstrate a 23–27% increase in the quality of independent work among students exposed to modern pedagogical approaches. The study highlights that a comprehensive and methodologically structured application of these technologies fosters lifelong learning competencies and enhances overall educational effectiveness.